Improving early childhood creativity through calligraphy activity from coffee dregs - Irma wati; Raden Rachmy Diana (Aṭfāluna: Journal of Islamic Early Childhood Education, 2021)
Creativity in early childhood at TK Pertiwi 26-13 Bogares Kidul is still low. This situation can be seen from the lack of imagination, initiative, and confidence in children to try new activities while learning. The purpose of this research is to increase the creativity, interest, and enthusiasm of children in learning calligraphy. Besides that, it is also to reduce coffee waste in the coffee shops around TK Pertiwi 26-13 Bogares Kidul. This research method uses PTK. The CAR uses the planning, implementation, observation, and reflection stages. The research location was in group B2 in TK Pertiwi 26-13 Bogares Kidul, with 14 students. The study using tools such as research sheets along with study evidence. For the study of evidence using qualitative analysis. The effect of the research conducted shows that children’s creativity increases. With the data in the first cycle, it was found that 35.7% of the children’s creativity level was then continued in the second cycle, which could be increased up to 80%. Therefore it was concluded that the children’s creativity experienced an increase through calligraphy activities from coffee dreg